2010
DOI: 10.1177/0142723710370530
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bilingual and monolingual children’s conversational repairs

Abstract: This study examined the conversational repair skills of 2-and 3-year-old FrenchEnglish bilingual children and monolingual French-speaking children. While the ability to respond to requests for clarification has been well researched in monolingual children, it has not been investigated among bilingual children except to examine their ability to repair breakdowns due to the use of a language not spoken by their interlocutor. The present study provides a direct comparison of bilingual and monolingual children's r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This offers some reassurance that young bilinguals-like young monolinguals-possess learning skills that can successfully get them started on expected vocabulary trajectories. There is also evidence that bilingual children match monolinguals in conversational abilities; for example, when somebody uses a confusing or mispronounced word, or says something ambiguous, bilingual children can repair the conversation with the same skill as monolinguals (Comeau, Genesee, & Mendelson, 2010).…”
Section: Are Bilingual Children More Likely To Have Language Difficulmentioning
confidence: 99%
“…This offers some reassurance that young bilinguals-like young monolinguals-possess learning skills that can successfully get them started on expected vocabulary trajectories. There is also evidence that bilingual children match monolinguals in conversational abilities; for example, when somebody uses a confusing or mispronounced word, or says something ambiguous, bilingual children can repair the conversation with the same skill as monolinguals (Comeau, Genesee, & Mendelson, 2010).…”
Section: Are Bilingual Children More Likely To Have Language Difficulmentioning
confidence: 99%
“…Introducing 2 languages does not interfere with acquisition of either, 22 -26 whether spoken or signed. 27…”
Section: What Will Give My Child the Best Chances Of Learning To Talk?mentioning
confidence: 90%
“…It can be claimed that stronger knowledge of L1 helps better acquisition of L2 (Yeung & Chan, 2012). Hence, these research studies have shown that it is more efficient to implement a bilingual early childhood education program rather than a program solely conducted in L1 or L2 as bilingualism does not interfere with the language development of bilinguals (Comeau et al, 2010). …”
Section: Literature Reviewmentioning
confidence: 95%
“…For example, a case study conducted by Dastgahian and Rostami (2013) showed that early bilingualism did not cause any delay in language acquisition process. Although it is accepted that L1 knowledge is usually stronger than L2 among preschoolers (Sevinc & Onkol, 2009;Unsworth, 2013), especially in vocabulary (Klassert, Gagarina, & Kauschke, 2014) since, for example, some image representations are more strongly connected to L1 than L2 (Jared, Poh, & Paivio, 2013), similarity has been found in rates and types of language processes such as phonology (Lin & Johnson, 2010) and ability to repair conversational breakdowns (Comeau, Genesee, & Mendelson, 2010). It also has been shown that bilingual children have the opportunity to assimilate new L2 sounds by matching them with familiar sounds in their L1, supporting the propositions of the Perceptual Assimilation Model (Ho, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%